FeOOH@Metal–Organic Framework Core–Satellite Nanocomposites for the Serum Metabolic Fingerprinting of Gynecological Cancers - Pei, Congcong; Liu, Chao; Wang, You; Cheng, Dan; Li, Rongxin; Shu, Weikang; Zhang, Chaoqi; Hu, Wenli; Jin, Aihua; Yang, Yannan; Wan, Jingjing (Angewandte Chemie International Edition, 2020)
High‐throughput metabolic analysis is of significance in diagnostics, while tedious sample pretreatment has largely hindered its clinic application. Herein, we designed FeOOH@ZIF‐8 composites with enhanced ionization efficiency and size‐exclusion effect for laser desorption/ionization mass spectrometry (LDI‐MS)‐based metabolic diagnosis of gynecological cancers. The FeOOH@ZIF‐8‐assisted LDI‐MS achieved rapid, sensitive, and selective metabolic fingerprints of the native serum without any enrichment or purification. Further analysis of extracted serum metabolic fingerprints successfully discriminated patients with gynecological cancers (GCs) from healthy controls and also differentiated three major subtypes of GCs. Given the low cost, high‐throughput, and easy operation, our approach brings a new dimension to disease analysis and classification. FeOOH@ZIF‐8 composites display enhanced ionization efficiency and size‐exclusion effect, enabling fast, sensitive, and selective LDI‐MS analysis of small metabolites in serum (1 μL) without pretreatment. Based on the extracted metabolic fingerprints, patients with three major gynecological cancers (ovarian, cervical, and endometrial cancer) were differentiated from healthy controls with high specificity and sensitivity.